Inflammation: Roles in Skeletal Muscle Atrophy - Yanan Ji; Ming Li; Mengyuan Chang; Ruiqi Liu; Jiayi Qiu; Kexin Wang; Chunyan Deng; Yuntian Shen; Jianwei Zhu; Wei Wang; Lingchi Xu; Hualin Sun (MDPI AG, 2022)
Various diseases can cause skeletal muscle atrophy, usually accompanied by inflammation, mitochondrial dysfunction, apoptosis, decreased protein synthesis, and enhanced proteolysis. The underlying mechanism of inflammation in skeletal muscle atrophy is extremely complex and has not been fully elucidated, thus hindering the development of effective therapeutic drugs and preventive measures for skeletal muscle atrophy. In this review, we elaborate on protein degradation pathways, including the ubiquitin-proteasome system (UPS), the autophagy-lysosome pathway (ALP), the calpain and caspase pathways, the insulin growth factor 1/Akt protein synthesis pathway, myostatin, and muscle satellite cells, in the process of muscle atrophy. Under an inflammatory environment, various pro-inflammatory cytokines directly act on nuclear factor-κB, p38MAPK, and JAK/STAT pathways through the corresponding receptors, and then are involved in muscle atrophy. Inflammation can also indirectly trigger skeletal muscle atrophy by changing the metabolic state of other tissues or cells. This paper explores the changes in the hypothalamic-pituitary-adrenal axis and fat metabolism under inflammatory conditions as well as their effects on skeletal muscle. Moreover, this paper also reviews various signaling pathways related to muscle atrophy under inflammatory conditions, such as cachexia, sepsis, type 2 diabetes mellitus, obesity, chronic obstructive pulmonary disease, chronic kidney disease, and nerve injury. Finally, this paper summarizes anti-amyotrophic drugs and their therapeutic targets for inflammation in recent years. Overall, inflammation is a key factor causing skeletal muscle atrophy, and anti-inflammation might be an effective strategy for the treatment of skeletal muscle atrophy. Various inflammatory factors and their downstream pathways are considered promising targets for the treatment and prevention of skeletal muscle atrophy.